Hubungan Mobilisasi Dini Dengan Penyembuhan Luka Post Operasi Apendiktomi Di Rumah Sakit Islam Purwokerto - Darmawan, Wisnu Dwi; Wibowo, Tophan Heri; Susanto, Amin (STIKES Karya Husada Kediri, 2024)
Background: One of the factors that influences the wound healing process due to appendectomy is early mobilization. Early mobilization has the effect of improving and facilitating blood circulation so that the supply of nutrients to the wound tissue can be adequate and the healing process will be faster. Objective: This study aims to determine the relationship between early mobilization and post-appendectomy wound healing at Purwokerto Islamic Hospital. Method: This research uses a non-experimental quantitative method with a descriptive correlation design. The approach used is cross sectional with non-probability sampling techniques. The data analysis test used in this research is the Spearman rank rho correlation test. Results: The results of this study indicate that early mobilization and wound healing in post-appendectomy patients at the RSU at Purwokerto Islamic Hospital, most of the early mobilization was adequate, 10 respondents (50%) with post-appendectomy patients' wound healing good, 12 respondents (60%). The results of the Spearman Rank test show that the p-value (0.000) < α 0.05, which means that H0 is rejected and Ha is accepted. The correlation coefficient test value = 0.845, so it was found that there was a relationship between early mobilization and post-appendectomy wound healing at the Purwokerto Islamic Hospital. Conclusion: There is a relationship between early mobilization and post-appendectomy wound healing at Purwokerto Islamic Hospital with a p-value of 0.000 and correlation coefficient = 0.845.